Trypanosoma cruzi: identification and characterization of a novel ribosomal protein L27 (TcrL27) that cross-reacts with an affinity-purified anti-Sm antibody - Perone, D. (2003)
Small nuclear ribonucleoproteins (snRNPs)are involved in trans-splicing processing of pre-mRNA in Trypanosoma cruzi. To clone T. cruzi snRNPs we screened an epimastigote cDNA library with a purified antibody raised against the Sm-binding site of a yeast sequence. A clone was obtained containing a 507 bp-insert with an ORF of 399 bp and coding for a protein of 133 amino acids. Sequence analysis revealed high identity with the L27 ribosomal proteins from different species including: Canis familiaris, Homo sapiens, Schizosaccharomyces pombe and Saccharomyces cerevisiae. This protein has not been previously described in the literature and seems to be a new ribosomal protein in T. cruzi and was given the code TcrL27. To express this recombinant T. cruzi L27 ribosomal protein in E. coli, the insert was subcloned into the pET32a vector and a 26 kDa recombinant protein was purified. Immunoblotting studies demonstrated that this purified recombinant protein was recognized by the same anti-Sm serum used in the library screening as well as by chagasic and systemic lupus erythemathosus (SLE) sera. Our results suggest that the T. cruzi L27 ribosomal protein may be involved in autoimmunity of Chagas disease.